2015
DOI: 10.1590/s0102-86502015001000011
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of airway management capacity of v-gel and cobra-PLA in anaesthetised rabbits

Abstract: PURPOSE:To evaluate the applicability and airway management capacity of v-gel ® and Cobra PLA in rabbit anaesthesia during assisted (AV) or controlled ventilation (CV). METHODS:This study was carried out in 44 adult New Zealand white rabbit. Baseline arterial pH, PaCO 2 and PaO 2 values were recorded. Anaesthesia was induced with 5 mg/kg xylasine and 35 mg/kg ketamine HCI combination. AV rabbits were assigned as;control (CG-AV; n=5), LMA (LMA-AV; n=5), cobra PLA (PLA-AV; n=5) and v-gel (v-gelAV; n=5). Rabbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…SGAD size was selected based on manufacturer guidelines. All rabbits in this study were of the same breed and while it is unknown if this breed was included during device design, airway management with this SGAD has been successful in this breed in other studies (14, 15). …”
Section: Discussionmentioning
confidence: 99%
“…SGAD size was selected based on manufacturer guidelines. All rabbits in this study were of the same breed and while it is unknown if this breed was included during device design, airway management with this SGAD has been successful in this breed in other studies (14, 15). …”
Section: Discussionmentioning
confidence: 99%
“…The colour of the other mucous membranes and the SpO 2 measured on the third digit were normal, suggesting that the lingual cyanosis was due to venous outflow obstruction caused by the v‐gel SGAD. This has been previously reported in cats (Prasse and others 2015) and rabbits (Crotaz 2013 ; Uzun and others 2015). Repositioning of the v‐gel SGAD and application of an ice pack on the tongue was sufficient to resolve the problem without further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LMAs in rabbits were easy to insert, but they had the potential of causing lingual cyanosis, gastric tympany, laryngeal oedema and air leak around the cuff (Bateman and others 2005, Kazakos and others 2007, Uzun and others 2015). These studies utilised an LMA that was specifically designed for human oropharyngeal anatomy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations